Formação de caudas maxwellianas no Contexto da rotação estelar - Freitas, Daniel Brito de (2009)
In this Thesis, we analyzed the formation of maxwellian tails of the distributions of the rotational velocity in the context of the out of equilibrium Boltzmann Gibbs statistical mechanics. We start from a unified model for the angular momentum loss rate which made possible the construction of a general theory for the rotational decay in the which, finally, through the compilation between standard Maxwellian and the relation of rotational decay, we defined the (_, _) Maxwellian distributions. The results reveal that the out of equilibrium Boltzmann Gibbs statistics supplies us results as good as the one of the Tsallis and Kaniadakis generalized statistics, besides allowing fittings controlled by physical properties extracted of the own theory of stellar rotation. In addition, our results point out that these generalized statistics converge to the one of Boltzmann Gibbs when we inserted, in your respective functions of distributions, a rotational velocity defined as a distribution